On the determinants of pro-environmental behavior: A literature review and guide for the empirical economist - Ann-Kathrin Blankenberg; Harm Alhusen (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2019)
This paper provides a systematic review of current economic and psychological studies on the determinants of PEB published up to 2017. Our normative understanding and study of PEB can benefit from an integral review of these research traditions. Consequently, we identify various determinants of PEB that can be classified into four major types: - Socio-demographic factors (personal capabilities) - Attitudinal (psychological) factors - Habits - Contextual factors (individual, social and institutional). Our paper shows that to understand the complex workings of PEB, it is no longer viable to study its determinants individually, but researchers must rather consider an interplay of these factors. In addition to the introduction of this intersectional approach, we show that measuring PEB in an adequate way requires the consideration of more than one or two distinct behaviors (multiple items) as the impact of the determinants differs depending on the analyzed behavior. PEB itself can also be distinguished into types of PEB (private vs public sphere behaviors, environmental activism). Additionally, our review gives an overview of the typical methodological approaches and systematizes the questions used to measure PEB. By combining results from economics and psychology, this work offers a starting point for a more intersectional and interdisciplinary understanding of PEB, and a guide for further empirical investigations.
Keywords: 330; determinants of pro-environmental behavior; ecological economics; review